2020
DOI: 10.3390/ijms21103587
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Experimental Models of Diabetic Nephropathy

Abstract: Diabetes prevalence is constantly increasing and, nowadays, it affects more than 350 million people worldwide. Therefore, the prevalence of diabetic nephropathy (DN) has also increased, becoming the main cause of end-stage renal disease (ESRD) in the developed world. DN is characterized by albuminuria, a decline in glomerular filtration rate (GFR), hypertension, mesangial matrix expansion, glomerular basement membrane thickening, and tubulointerstitial fibrosis. The therapeutic advances in the last years have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 98 publications
3
35
0
1
Order By: Relevance
“…It enhances both neutrophil and macrophage migration into the tubulointerstitial regions, which is detrimental to kidney health ( 7 ). Studies involving human biopsy specimens and animal models have reported that macrophage infiltration is a characteristic of DN, confirming the concept that inflammation plays a crucial role in the pathogenesis of DN ( 33 ).…”
Section: Discussionsupporting
confidence: 57%
“…It enhances both neutrophil and macrophage migration into the tubulointerstitial regions, which is detrimental to kidney health ( 7 ). Studies involving human biopsy specimens and animal models have reported that macrophage infiltration is a characteristic of DN, confirming the concept that inflammation plays a crucial role in the pathogenesis of DN ( 33 ).…”
Section: Discussionsupporting
confidence: 57%
“… 1 , 2 Like many renal diseases, DN is characterized by proteinuria, which is frequently induced by death and loss of podocytes, followed by reduced glomerular filtration, mesangial matrix expansion glomerulosclerosis and the consequent kidney failure. 3 , 4 Initiation and progression of DN is not always predictable and the DN development is a long-term process occurring gradually over many years. 5 Several mechanisms such as activation of the profibrotic transforming growth factor beta (TGF-β) signaling, 6 suppression in fibroblast growth factor receptor 1 signaling, 7 loss of endothelial glucocorticoid receptor, 8 and dysregulated central metabolism 9 have been reported to be associated with DN development.…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of diabetic kidney disease is complicated and involved many factors, including genetic factors, hypertension, abnormalities of renal hemodynamics, as well as metabolism of vasoactive substances ( Lu et al, 2019 ). Diabetic nephropathy (DN), the major cause of chronic kidney disease, is characterized by albuminuria, lowered glomerular filtration rate, hypertension, and mesangial matrix expansion in addition to tubulointerstitial fibrosis ( Giralt-Lopez et al, 2020 ). The progression of DN has been suggested to attribute to various pathological mechanisms, including inflammation and fibrosis ( Calle and Hotter, 2020 ).…”
Section: Introductionmentioning
confidence: 99%